Analysis of Students' Needs for Guidance and Counseling Services in Higher Education in Overcoming Students' Mental Well-Being: A Systematic Literature Review - Lena Marianti; Sudarwan Danim; Nurul Astuti Yensy (Bulletin of Indonesian Islamic Studies, 2025)
This research aims to analyze students' needs for guidance and counseling (BK) services in higher education in order to improve students' mental well-being. The research method used is Systematic Literature Review (SLR), by examining eight relevant scientific articles published between 2020 and 2025. Data sources were obtained through the ScienceDirect, ResearchGate, SpringerLink, and Google Scholar databases, using the keywords "guidance and counseling in higher education", "student well-being", and "counseling needs". The research procedure includes the stages of identification, selection, data extraction, and thematic synthesis to find consistent patterns and conclusions. The results show that students have a high need for BK services which include academic, social, career, and psychological aspects. BK services have proven to play an important role in helping students manage stress, increase self-awareness, develop resilience, and strengthen mental well-being. However, the implementation of BK services in universities still faces challenges, such as limited human resources, lack of student awareness of the function of BK, and lack of institutional support. Technology-based innovations, such as e-counseling and artificial intelligence (AI) integration, are considered to be able to expand access to services and increase the effectiveness of counseling, especially for students who are reluctant to do face-to-face counseling. This research confirms that BK services are a strategic component in the higher education system that supports the development of character and mental well-being of students. Therefore, it is necessary to strengthen the capacity of counselors, innovate technology-based services, and a holistic approach that integrates academic, psychological, social, and spiritual aspects.